PELATIHAN PENINGKATAN MOTIVASI BELAJAR BAHASA INGGRIS MAHASISWA UNIVERSITAS dr. SOEBANDI DI PRIMA ENGLISH JEMBER - Lutfiah; Akhmad Nuris Hidayat; Hamliyah (P3M Sekolah Tinggi Agama Islam Miftahul Ulum, 2024)
Low motivation in learning can make learning difficult. This difficulty arises because of the lack of encouragement to strive to achieve the target. As an English educator, this can be done by conveying learning objectives before learning begins. This also needs to be followed by appropriate learning activities so that motivation can be built. The Prima English course institution has a solution by holding socialization and training in English learning motivation so that students have a strong passion and goal to learn English. The activity will last for two days which on the first day there is socialization and the next day is training.